2018
DOI: 10.1007/s00464-018-6386-7
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic truncal vagotomy versus surgical revision of the gastrojejunal anastomosis for recalcitrant marginal ulcers

Abstract: Our results demonstrate that thoracoscopic vagotomy may be a better alternative with decreased operative times and similar effectiveness. However, further prospective observational studies with a larger patient population would be beneficial to evaluate complication rates and ulcer recurrence rates between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Treatment of marginal ulcer consists of elimination of risk factors, PPI, and regular endoscopic monitoring 9 . They are rarely refractory to medical management which brings up the necessity of revision surgery that includes resection and reconstruction of anastomosis 9,10 . Emergency laparotomy is necessary when patient presents with perforation of marginal ulcer; perforated ulcer can be managed with simple closure and omental patch closure 1,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of marginal ulcer consists of elimination of risk factors, PPI, and regular endoscopic monitoring 9 . They are rarely refractory to medical management which brings up the necessity of revision surgery that includes resection and reconstruction of anastomosis 9,10 . Emergency laparotomy is necessary when patient presents with perforation of marginal ulcer; perforated ulcer can be managed with simple closure and omental patch closure 1,9 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found no significant difference in recurrence rate (15% vs 14%, P = .2575) in their cohort of 20 patients. 15 Chang et al examined 11 patients who underwent hand-sewn revision of GJ with TV and found that none of the patients had recurrence at a mean follow-up of 28.0 months. 16…”
Section: Discussionmentioning
confidence: 99%
“…The authors found no significant difference in recurrence rate (15% vs 14%, P = .2575) in their cohort of 20 patients. 15 Chang et al examined 11 patients who underwent hand-sewn revision of GJ with TV and found that none of the patients had recurrence at a mean follow-up of 28.0 months. 16 An international survey of bariatric surgeons indicated that revision of the GJ anastomosis was the preferred method of revision for chronic MU disease.…”
Section: Discussionmentioning
confidence: 99%
“…For patients resistant to marginal ulcer treatment, even with appropriate measures, truncal vagotomy may present itself as a viable stand-alone strategy for healing before considering anastomotic revision. Truncal vagotomy, first described in 1947 for healing a GJA ulcer [87] , can be conducted either laparoscopically [88] or thoracoscopically [89][90][91] . In a study by Bonanno et al [90] , where 20 patients with resistant marginal ulceration underwent either GJA revision or thoracoscopic truncal vagotomy (TTV), results indicated comparable ulcer recurrence rates between GJ revisions (15%) and TTV (14%).…”
Section: Truncal Vagotomymentioning
confidence: 99%